Effect of Work Discipline and Work Motivation on Employee Performance - Ira Yusnita Ali; Rusdiana Simamora (Almana : Jurnal Manajemen dan Bisnis, 2022)
The Covid-19 pandemic has an impact on employee anxiety to leave the house for activities for a long period of time, this condition triggers a decrease in work discipline in the company which is known from employees arriving late, not being in place during working hours and high levels of employee absenteeism. Another phenomenon is a decrease in employee work motivation which is known from employees who are less diligent, unfocused, less responsive, and less proficient at work. The phenomenon of work discipline and work motivation has an impact on decreasing employee performance. This research aim is to test and analyze the effect of work discipline and work motivation on employee performance at PT. Samawood Utama Works Industries Medan during the covid 19 pandemic. The method used is a quantitative approach with quantitative descriptive research. Methods of collecting data were interviews and questionnaires. The data analysis method used is multiple linear regression. The results obtained are work discipline and motivation individually and simultaneously affect the performance of employees. The ability of the employee performance variable to explain work discipline and work motivation is 73.4%, the remaining 26.6% is explained by variables not observed in this research such as leadership, work environment, and others.